Persistent Misallocation and the Returns to Education in Mexico - Levy, Santiago; Lopez-Calva, Luis Felipe (World Bank, Washington, DC, 2019)
Over the last two decades, Mexico has experienced macroeconomic stability, an open trade regime, and substantial progress in education. Yet average workers' earnings have stagnated, and earnings of those with higher schooling have fallen, compressing the earnings distribution and lowering the returns to education. This paper argues that distortions that misallocate resources toward less-productive firms explain these phenomena, because these firms are less intensive in well-educated workers compared with more-productive ones. It shows that while the relative supply of workers with more years of schooling has increased, misallocation of resources toward less productive firms has persisted. These two trends have generated a widening mismatch between the supply of, and the demand for, educated workers. The paper breaks down worker earnings into observable and unobservable firm and individual worker characteristics, and computes a counterfactual earnings distribution in the absence of misallocation. The main finding is that in the absence of misallocation average earnings would be higher, and that earnings differentials across schooling levels would widen, raising the returns to education. A no-misallocation path is constructed for the wage premium. Depending on parameter values, this path is found to be rising or constant, in contrast to the observed downward path. The paper concludes arguing that the persistence of misallocation impedes Mexico from taking full advantage of its investments in the education of its workforce.